Lean start-up awareness and effect on entrepreneurial intentions among Malaysian youths - Ekpe, Isidore; Mat, Norsiah; Yaacob, Mohd Rafi; Abdul Rahim, Mohammad Nizamuddin (2018)
In an attempt to develop greater interest in enterprise start-up, this study examines the level of awareness of lean start-up model and its effect on entrepreneurial intentions among Malaysian youths. In this study, we argue that greater entrepreneurial interest could be ignited in the youths if lean start-up model is applied in teaching and learning. Using a survey, data were collected from 191 university students at three universities in Malaysia peninsula. These data were analysed with descriptive statistics and regression methods. We found that majority of the students were not aware of lean start-up model. Our research also established a significant positive effect of lean start-up on entrepreneurial intentions among Malaysian youths. We recommend that the government and university authorities should draft appropriate strategies (e.g. inclusion in syllabus) that will engender greater awareness and adoption of lean start-up, especially among students and lecturers, for enterprise creation in the country.